(untitled) (Research, Society and Development, 2021)
Active Methodologies (AM’s), which emerged in the last decades of the twentieth century, can be understood as a set of methods that seek to develop the autonomy of students in the process of acquiring knowledge. Thinking about it, through the theoretical contribution of authors such as Moran (2015), Bacich (2015), Masetto (2010), Dewey (2010) and Freire (2009), we present AM’s as our object of study. For this, due to the revisionary nature of the method used, we resorted to descriptive research, with a qualitative approach. In turn, these conceptual and methodological bases have led us to the following problems: What are AM’s and in which types are they categorized? What are the characteristics of the active study? And, finally, what are their contributions to student learning? Starting from these questions, this article aims, in a first moment, to present some types of AM’s and, in a second moment, the activities carried out in the year 2020 in the workshop “Active methodologies: learning through rotation by seasons, rotational laboratory, and inverted classroom”, linked to the Extension Project “ Active Methodologies in the teaching and learning process at the Elementary School Maria Gonçalves da Rocha Leal in Limoeiro do Norte-CE ” by the Pedagogy Course of the College of Philosophy Dom Aureliano Matos (FAFIDAM / UECE). According to our preliminary analyzes, the use of AM’s is configured as an auxiliary tool in the teaching-learning process. For this reason, it is important to emphasize that no methodology should be held responsible, in isolation, for the success or failure of the students, since there are numerous adversities that permeate the Brazilian educational context, especially in public schools.